The Effect of Fermentation Duration and Concentration Variation of Gyrinops versteegii Leaf Decoction on The Alcohol Content of Gyrinops versteegii Leaf Decoction Water Kefir and Its Integration with The Qur'anic Interpretation - Munajib, Achmad (Proceeding International Conference on Science and Engineering, 2021)
Abstract. Water kefir is one of the drinks made from the fermentation of water kefir seeds. Alternative media is important to be found for product development. One of the potential media is agarwood leaf decoction (Gyrinops versteegii). The purpose of this research was to determine the effect of fermentation duration and concentration variations on the alcohol content of Gyrinops versteegii leaf decoction water kefir and its integration with QS. Al-Maidah [5]: 90 and QS. Al-A'raf [7]: 31. This research is an experiment with a completely randomized design (CRD) factorial pattern. The first factor was the concentration of agarwood leaf decoction (5%, 10%, 15%, and 20%). The second factor is the fermentation time (18 hours, 21 hours, and 24 hours). The second factor was combined with the addition of 6% sucrose, 5% water kefir seeds, and incubated at room temperature. The results showed that the length of fermentation and the variation in the concentration of agarwood leaf decoction had a significant effect on alcohol content with a significance value of <0.05. the alcohol content produced after fermentation is 0.4% -0.8%. The integration of these results used the interpretation method of the maudhui interpretation so that the conclusion was that beverage products below 1% alcohol content were halal and good products that were following the values contained in the Quran.